Overexpression of a Hevea brasiliensis ErbB-3 Binding protein 1 Gene Increases Drought Tolerance and Organ Size in Arabidopsis - Cheng, Han; Chen, Xiang; Zhu, Jianshun; Huang, Huasun (Frontiers in Plant Science, 2016)
Rubber trees are economically important tropical tree species and the major source of natural rubber, which is an essential industrial material. This tropical perennial tree is susceptible to cold stress and other abiotic stresses, especially in the marginal northern tropics. Recent years, the genome sequencing and RNA-seq projects produced huge amount of sequence data, which greatly facilitated the functional genomics study. However, the characterization of individual functional gene is in urgent demands, especially for those involved in stress resistance. Here we identified and characterized the rubber tree gene ErbB-3 binding protein 1, which undergoes changes in expression in response to cold, drought stress and ABA treatment. HbEBP1 overexpression (OE) in Arabidopsis increased organ size, facilitated root growth and increased adult leaf number by delaying the vegetative-to-reproductive transition. In addition, HbEBP1 OE enhanced the resistance of the Arabidopsis plants to freezing and drought stress, demonstrating that this gene participates in the regulation of abiotic stress resistance. RD29a, RD22 and CYCD3;1 expression was also greatly enhanced by HbEBP1 OE, which explains its regulatory roles in organ size and stress resistance. The regulation of drought stress resistance is a novel function identified in plant EBP1 genes, which expands our understanding of the roles of EBP1 gene in response to the environment. Our results provide information that may lead to the use of HbEBP1 in genetically engineered crops to increase both biomass and abiotic stress resistance.